Methylmercury content in soil and litter from the Amazonian rainforest and its potential fate during forest fires - Fostier, Anne Helene; Amouroux, David; Tessier, Emmanuel; Viana, José Lucas Martins; Richter, Larissa (Frontiers in Environmental Chemistry, 2023)
Methylmercury in soils and vegetation from the Amazonian rainforest is still poorly studied. Hence, the aim of this work was to determine the total mercury [THg] and methylmercury [MeHg] concentrations in litter and surface soil, MeHg deposition via litterfall, and the MeHg fate during a forest fire in the Amazonian rainforest. Sampling of litter, soil (0–1, 1–2, and 2–5 cm), and ash was carried out before (BB) and after (AB) a prescribed forest fire. The results showed a low [THg] (34 ± 8 ng g-1) and [MeHg] (0.16 ± 0.03 ng g-1) value in litter, with a correspondingly low estimate of the MeHg litterfall flux (0.13 ± 0.03 μgm-2 yr-1) which has been probably underestimated due to potential losses during the field experiment. In ashes, [THg] and [MeHg] values were 23 ± 8 ng g-1 and 0.11 ± 0.04 ng g-1, respectively. Although a significant part of Hg contained in the biomass was lost during the fire, the [MeHg]/[THg] ratio was not affected by it and was the same in litterfall and ash (∼0.5%). In soil, the average [THg] BB value was 149 ± 12 ng g-1 in the three layers and [MeHg] was between 0.8 and 1.0 ng g-1. The forest fire only affected the superficial soil, with a significant decrease of [THg] and [MeHg] in the 0-1 cm layer. Similarly, the decrease of the [MeHg]/[THg] ratio in the surface soil layer suggested that MeHg was more readily emitted or degraded than the other Hg species present.